Optimalisasi Peran Perawat Melakukan Screening Palliative Care untuk Menerapkan Intervensi Keperawatan Paliatif - Suksi Riani; Ismonah Ismonah; Fransisca Gloria (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
The increasing number of patients chronic and terminal disease such as cancer,COPD, stroke, hearth failure, degenerative desease, HIV/AIDS that requirepalliative care according to the 2007 Ministry of Health Policy. The application ofpalliative care in Indonesia is not optimal because there are still many nurses andthe community who do not know about palliative care. The purpose is to optimizethe role of nurses in screening palliative care and providing palliative nursinginterventions. This study method uses sharing knowledge and training withmeasured their level of knowledge about palliative care. The stages includesocialization, pre test, presentation, demonstrations, post test and follow up plans.The result showed that the majority aged 41-50 years old, female gender, educationbachelor, length of work 11-20 years, increase knowledge majority being good(60%). This community service is important to improve the application ofpalliative care in health services and in the community.